Revisão taxonômica do gênero Actinopus perty, 1833, com a descrição de quatro espécies novas de Missullena walckenaer, 1805 (Araneae, Mygalomorphae, Actinopodidae) - MIGLIO, Laura Tavares (2014)
Actinopus Perty, 1833 is characterized and redescribed, harboring sixty-three species occurring from Panama to Argentina. Seventeen previously known species are redescribed: A. tarsalis Perty, 1833; A. rufipes (Lucas, 1834); A. longipalpis C. L. Koch, 1842; A. nattereri (Doleschall, 1871); A. insignis (Holmberg, 1881); A. crassipes (Keyserling, 1891); A. robustus (O. Pickard-Cambridge, 1892); A. wallacei F. O. P.- Cambridge, 1896; A. princeps Chamberlin, 1917, A. xenus Chamberlin, 1917; A. fractus Mello-Leitão, 1920; A. paranensis Mello-Leitão, 1920; A. pusillus Mello-Leitão, 1920; A. dubiomaculatus Mello-Leitão, 1923; A. trinotatus Mello-Leitão, 1938; A. cucutaensis Mello-Leitão, 1941; and A. echinus Mello-Leitão, 1949. Forty-four new species are described: Actinopus castelo n. sp., A. apalai n. sp., A. mairinquensis n. sp., A. obidos n. sp., A. buritiensis n. sp., A. pinhao n. sp., A. ducke n. sp., A. hirsutus n. sp., A. jaboticatubas n. sp., A. confusus n. sp., A. pampulha n. sp., A. candango n. sp., A. paraitinga n. sp., A. cornelli n. sp., A. vilhena n. sp., A. harveyi n. sp., A. itapitocai n. sp., A. ipioca n. sp., A. itaqui n. sp., A. xingu n. sp., A. mesa n. sp., A. caxiuana n. sp., A. utinga n. sp., A. emas n. sp., A. bocaina n. sp., A. guajara n. sp., A. apiacas n. sp., A. jamari n. sp. from Brazil; A. laventana n. sp. and A. calamuchita n. sp. from Argentina and Uruguay; A. lomalinda n. sp. from British Guiana and Colombia; A. concinnus n. sp. from Venezuela and Brazil; A. palmar n. sp. and A. loscocos n. sp. from Argentina; A. panguana n. sp. from Peru. The females of A. dubiomaculatus and A. cucutaensis and the unknown males of A. nattereri are described for the first time. New records are presented for A. crassipes; A. dubiomaculatus; A. fractus; A. nattereri; A. paranensis; A. princeps, A. pusillus, A. robustus and A. wallacei. Most of the species presently recognized were included in eleven informal groups based mainly in male palpal characters. A key for these groups plus three species, not included in any group, but known from males, is presented.